Identification of Novel α-Glucosidase Inhibitors by Screening Libraries Based on N- [4-(Benzyloxy) Benzoyl] Alanine Derivatives - Kundu, B.; Rastogi, S.K.; Ahmad, R.; Srivastava, A.K. (Combinatorial Chemistry & High Throughput Screening, 2002)
A library of 72 compounds related to N- [4-(benzyloxy) benzoyl]alanine (I) was synthesized, prepared and screened for α-glucosidase inhibitory activity. Four compounds showed potent inhibition, six compounds moderate inhibition, and 16 were weak inhibitors. One compound, N- [4-(benzyloxy) benzoyl] serine, was found to be a potent inhibitor of α-glucosidase with 100% inhibition at 1μM. This inhibitor was at least five times more potent than the lead compound I.
Keywords: glucosidase inhibitor